Team characteristics beneficial for Open Innovation projects - Krylova, Alena (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
This study discusses the importance of creating Open Innovation (OI) teams for optimizing costs of Research and Development (R&D), dividing risks and maximizing profits. The purpose of this study is to determine team characteristics beneficial for successful OI project, with the emphasis on the fact that such teams are formed of professionals belonging to different organizations, both private and state-owned, with different educational and professional backgrounds and personal qualities. This purpose is supported by three sub-objectives: to observe the phenomenon of OI and its implementation in emerging economies, particularly in Russia; to specify professional and personal competencies of OI team members essential for the successful collaboration; and to identify the role of the leader in OI teams. The theoretical part of this study consists of knowledge from academic literature related to OI, cross-functional and innovation teams and leadership in innovation. The practical part of the study is presented in the form of multiple case study, and the empirical research is based on six semistructured interviews collected in October 2014 from the CEOs, Innovation Managers and Technical Directors of innovation companies participating actively in OI projects. The findings of the study demonstrate that many of the necessary competencies are equal for innovation or cross-functional teams and OI teams, such as professionalism and communication skills. However, due to the specific nature of OI, additional personal characteristics were recognized as beneficial for OI teams, such as flexibility, empathy and success-orientation. The role of the leader is also considered as a critical success factor for OI teams, with the emphasis on flexibility and autonomy. The findings of the study contribute to understanding the connection between notions of team member, team climate and team leader, and its influence on OI project success. Thus, the main purpose of the study is providing support for existing knowledge on OI teams and developing new insights into this newly emerged topic.